2011
DOI: 10.4081/jphia.2011.e20
|View full text |Cite
|
Sign up to set email alerts
|

Early alcohol use and problem drinking among students in Zambia and Uganda

Abstract: Excessive alcohol use is a serious public health concern worldwide, but less attention has been given to the prevalence, risk and protective factors, and consequences of early alcohol use in low-income, developing countries. The purpose of this study was to determine the associations between early alcohol use, before age 13, and problem drinking among adolescents in Uganda and Zambia. Data from students in Zambia (n=2257; 2004) and Uganda (n=3215; 2003) were obtained from the cross-sectional Global School-Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
(34 reference statements)
2
23
0
Order By: Relevance
“…For example, cultural and community norms such as acceptance and ease of obtaining alcohol (Swahn et al, 2011) are demonstrated by the fact that 90% of Zambian youth report that alcohol is “very easy” to obtain in their community (Nkowane et al, 2004). In general, community level risk factors have been linked to HIV infection in young women (Gabrysch, Edwards, & Glynn, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, cultural and community norms such as acceptance and ease of obtaining alcohol (Swahn et al, 2011) are demonstrated by the fact that 90% of Zambian youth report that alcohol is “very easy” to obtain in their community (Nkowane et al, 2004). In general, community level risk factors have been linked to HIV infection in young women (Gabrysch, Edwards, & Glynn, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The prevalence of income was three to five minimum wages and the socioeconomic status was C. In other studies (1,2,5) students who reported higher income consumed more alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…3 In Zambia, it is estimated that 49.3% of the population above age 15 indulge in heavy drinking (five or more drinks) on at least one occasion in the past 30 days (60.1% for men and 24.8% for women) 4 , and problem drinking is greater among teen girls than teen boys. 5,6 Studies conducted in Zambia and the Republic of South Africa (RSA) found misperceptions about alcohol use during pregnancy. 7,8 Alcohol use during pregnancy has been found to be correlated with many negative health outcomes for the neonate (e.g., physical and cognitive defects 9 and neurodevelopmental abnormalities), 10 and for the mother (e.g., decreased production of breast milk).…”
Section: Introductionmentioning
confidence: 99%